Language, Dialect And Register Sociolinguistic Perspective - I Made Budiarsa (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2015)
Sociolinguistics pays attention to the social aspects of human language. Sociolinguistics discusses the relationship between language and society. In the following part of this paper, it will be focussed on the use of (1) language (2) dialects, (3) language variation, (4) social stratification, (5) register. This discussion talks about the five types of those topics because they are really problematic sort of things, which relate the social life of the local people. In relation to this, the most important point is to distinguish the terms from one to another. There are three main points to discuss: language, dialects and register. Languages which are used as medium of communication have many varieties. These language variations are created by the existence of social stratification in the community. Social stratification will determine the form of language use by the speakers who involve in the interaction. The language variation can be in the form of dialects and register. Dialect of a language correlates with such social factors such as socio-economic status, age, occupation of the speakers. Dialect is a variety of a particular language which is used by a particular group of speakers that is signaled by systematic markers such as syntactical, phonological, grammatical markers. Dialects which are normally found in the speech community may be in the forms of regional dialect and social dialect. Register is the variation of language according to the use. It means that where the language is used as a means of communication for certain purposes. It depends entirely on the domain of language used. It is also a function of all the other components of speech situation. A formal setting may condition a formal register, characterized by particular lexical items. The informal setting may be reflected in casual register that indicates less formal vocabulary, more non-standard features, greater instances of stigmatized variables, and so on.Keywords: language, dialect, register and sociolinguistic.